Variability of stem CO2 efflux response to temperature over the diel period. (28th December 2018) - Darenova, Eva; Szatniewska, Justyna; Acosta, Manuel; Pavelka, Marian
Abstract: This study presents results from continuous measurements of stem CO2 efflux carried out for seven growing seasons in a young Norway spruce forest. The objective of the study was to determine differences in temperature sensitivity of stem CO2 efflux ( Q 10 ) during night (when sap flow is zero or nearly zero), during early afternoon (when the maximum rate of sap flow occurs) and during two transition periods between the aforementioned periods. The highest Q 10 was recorded during the period of zero sap flow, while the lowest Q 10 was observed in period of the highest sap flow. Calculating Q 10 using only data from the period of zero sap flow resulted in a Q 10 that was higher by as much as 19% compared with Q 10 calculated using 24 h data. On the other hand, basing the calculation on data from the period of the highest sap flow yielded 5.6% lower Q 10 than if 24 h data were used. Considering that change in CO2 efflux lagged in time behind changing stem temperature, there was only a small effect on calculated Q 10 for periods with zero and the highest sap flow. A larger effect of the time lag (by as much as 15%) was observed for the two transition periods. Stem CO2 efflux was modelled based on the night CO2 efflux response to temperature. This model had a tendency to overestimate CO2 efflux during daytime, thus indicating potential daytime depression of stem CO2 efflux compared with the values predicated on the basis of temperature caused by CO2 transport upward in the sap flow. This view was supported by our results inasmuch as the overestimation grew with sap flow that was modelled on the basis of photosynthetically active radiation and vapour pressure deficit.